The Economic Impact of Capital and Innovation on MSME Income: The Mediating Role of Digital Disruption - Swara, Pande Made Veda Agasta; Gorda, Eddy Supriyadinata (International Journal of Economics Development Research (IJEDR), 2025)
The development of digital technology and changes in consumer behavior have triggered the need for research that examines the influence of capital and innovation on the income of Micro, Small, and Medium Enterprises (MSMEs) with digital disruption as a mediating variable. This study aims to analyze the relationship and provide insight into how MSMEs can adapt to an increasingly digital business environment. This research was conducted in Denpasar City, Bali Province. The selection of the research location was based on considerations that Denpasar City is the most densely populated city/area in Bali. The Purposive Sampling technique in this study sets certain criteria. The number of samples used in this study was 92 respondents who were each MSME owner. The data collection method was with a questionnaire with a Likert scale and tested with the SmartPLS application for descriptive analysis and inferential analysis. The findings of this study are that capital does not have a significant positive effect on income, Innovation does not have a positive and significant effect on income, Digital disruption strategies are able to mediate capital on MSME income in Denpasar City, Digital disruption strategies are not able to mediate innovation on MSME income in Denpasar City. This study concludes that the existence of capital alone is not enough to increase the income of MSMEs, this ineffectiveness is caused by the less than optimal product innovation carried out by MSMEs in Denpasar City so that the results achieved are not optimal, Digitalization has become a transformational force in various sectors, including the MSME sector.